Recent Advances in Zinc Oxide Nanoparticles: Synthesis Methods, Characterization Techniques, and Emerging Applications - Bhosale, Sachin; Kannor, Nikita; Shinde, Nirmala; Sahane, Nikita (Current Catalysis, 2024)
Zinc oxide (ZnO) is an inorganic compound with unique physicochemical characteristics that make it versatile and suitable for various applications, especially in the form of nanoparticles (NPs). ZnO nanoparticles (ZnO NPs) exhibit distinct properties and are produced through diverse techniques, making them valuable for applications ranging from consumer goods to medical and catalytic uses. The increasing popularity of ZnO NPs is driven by novel synthesis methods that allow for modification of chemical composition and control over size and shape, thereby enhancing their properties and expanding their applications. The catalytic activity of ZnO NPs is influenced by parameters such as oxophilicity, large surface area, amphoteric nature, and the zinc cation's ability to approach activated starting material supports, making them viable heterogeneous catalysts for a variety of applications. Various analytical techniques, including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) analysis, atomic force microscopy (AFM), and many more, are used to characterize the nanoparticles. This article explores various synthesis methods and characterization techniques and focuses on the catalytic activities of ZnO NPs
Keywords: characterizations